Analysis of low-density lipoprotein receptor gene mutations in a Chinese patient with clinically homozygous familial hypercholesterolemia - 曹守春 王绿娅 秦彦文 蔺洁 吴邦俊 刘舒 潘晓冬 杜兰平 陈保生 (Chinese medical journal, 2003)
Objective To screen the point mutation of the low-density lipoprotein receptor (LDL-R) gene in Chinese familial hypercholesterolemia (FH) patients, characterize the relationship between the genotype and the phenotype and discuss the molecular pathological mechanism of FH.Methods A patient with clinical phenotype of homozygous FH and her parents were investigated for mutations in the promoter and all eighteen exons of the LDL-R gene. Screening was carded out using Touch-down PCR and direct DNA sequencing; multiple alignment analysis by DNASIS 2. 5 was used to find base alteration, and the LDL-R gene mutation database was searched to identify the alteration.In addition, the apolipoprotein B gene (apo B) was screened for known mutations (R3500Q) that cause familial defective apo B100 (FDB) by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP).Results Two new heterozygous mutations in exons 4 and 9 of the LDL-R gene were identified in the proband (C122Y and T3831) as well as her parents Both of the mutations have not been published in the LDL-R gene mutation database. No mutation of apo B100 (R3500Q) was observed.Conclusion Two new mutations (C112Y and T3831) were found in the LDL-R gene, which may result in FH and may be particularly pathogenetic genotypes in Chinese people.